Colombia - Country Note on Climate Change Aspects in Agriculture - World Bank (Washington, DC, 2012)
This country note briefly summarizes information relevant to both climate change and agriculture in Colombia, with focus on policy developments (including action plans and programs) and institutional make-up. Like most countries in Latin America, Colombia has submitted one national communication to the United Nations Framework Convention on Climate Change (UNFCCC) with a second one under preparation. Agriculture (including land use change and forestry) significantly contributes to total green house gas (GHG) emissions in the country. The emission reduction potential of the agricultural sector (including land use change and forestry) is significant and not yet sufficiently explored in the country. Colombia does not count with a single Clean Development Mechanism (CDM) projects in the agricultural sector. Agriculture is highly vulnerable to weather extremes, in particular on the Caribbean coast, where the threat of floods is prevalent. Reducing vulnerability to climate change is of utmost importance in the agricultural sector in Colombia, considering the role the sector plays in food security and livelihoods of rural populations.